2001
DOI: 10.1021/es0105562
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Oxidation of Arsenite in a Hot Spring Ecosystem, Yellowstone National Park

Abstract: Geothermal springs within Yellowstone National Park (YNP) often contain arsenic (As) at concentrations of 10-40 microM, levels that are considered toxic to many organisms. Arsenite (As(III)) is often the predominant valence state at the point of discharge but is rapidly oxidized to arsenate (As(V)) during transport in shallow surface water. The current study was designed to establish rates and possible mechanisms of As(III) oxidation and to characterize the geochemical environment associated with predominant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
203
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(224 citation statements)
references
References 28 publications
14
203
4
1
Order By: Relevance
“…Arsenite concentrations and percentage As(III) of total As in the spring waters are highly variable (Table 1), as in other geothermal areas (Ballantyne and Moore, 1988), and probably reflect the degree to which the spring waters have been oxidized upon ascent to the surface by abiotic and biotic processes (cf., Langner et al, 2001). As(III) concentrations are highest in the highest temperature SPR1-6 group, and these are the lowest pH spring waters sampled (pH = 6.42-6.75).…”
Section: Characteristics Of Spring Watersmentioning
confidence: 84%
See 1 more Smart Citation
“…Arsenite concentrations and percentage As(III) of total As in the spring waters are highly variable (Table 1), as in other geothermal areas (Ballantyne and Moore, 1988), and probably reflect the degree to which the spring waters have been oxidized upon ascent to the surface by abiotic and biotic processes (cf., Langner et al, 2001). As(III) concentrations are highest in the highest temperature SPR1-6 group, and these are the lowest pH spring waters sampled (pH = 6.42-6.75).…”
Section: Characteristics Of Spring Watersmentioning
confidence: 84%
“…These waters can contain high concentrations of As that arises from dissolution of As gas or As-bearing minerals in magmatic and hydrothermal waters and subsequent mixing of these waters with meteoric waters (Ellis and Mahon, 1977;Welch et al, 1988;Webster and Nordstrom, 2003). In these waters, As generally occurs either as As(III) or As(V), depending on pH, redox potential and the availability of As(III)-oxidising bacteria (Langner et al, 2001;Webster and Nordstrom, 2003) Other elements that are concentrated in geothermal brines and related meteoric waters, such as B and F, may also pose a threat to human health should they be ingested (Webster, 1999;Katsoyiannis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent follow-up characterizations of this organism and this process failed to materialize; however, approximately 2 decades later, Santini et al (52) described the isolation and initial characterization of a Rhizobiumlike bacterium (strain NT-26) that could grow chemolithoautotrophically with As III as a sole electron donor for energy generation and with CO 2 as a sole carbon source. Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6, 13, 40); and, most recently, in anoxic photosynthesis (21, 33). Likewise, progress has been made in the understanding of the biochemistry of the As III oxidase enzyme (1,14,37 oxidase structural genes were later cloned from the above-mentioned Rhizobium NT-26 organism (53).…”
mentioning
confidence: 99%
“…Subsequent follow-up characterizations of this organism and this process failed to materialize; however, approximately 2 decades later, Santini et al (52) described the isolation and initial characterization of a Rhizobiumlike bacterium (strain NT-26) that could grow chemolithoautotrophically with As III as a sole electron donor for energy generation and with CO 2 as a sole carbon source. Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6,13,40); and, most recently, in anoxic photosynthesis (21,33 (28,31) indicated the role and importance of the sensor kinase AioS and its putative regulatory partner AioR (a bacterial enhancer binding protein), direct proof of these two proteins working together as part of a putative As III signal perception and transduction cascade was just recently provided by Sardiwal et al (54), who demonstrated the autophosphorylation of an AioS component and the AioS-specific phosphorylation of AioR. Recently, our work has expanded this regulatory model to now include a third component, AioX, which is a periplasmic As III binding protein that is also essential for aioBA expression (39 …”
mentioning
confidence: 99%
“…Although problems in the USA are not as severe, moderate to > 50 pg L' 1 naturally occurring concentrations o f As are commonly found in groundwater throughout the western USA (Welch et al, 2000). The high content o f As in hot springs is notable; extremely high As concentrations have been reported in some groundwater from areas o f thermal activity (Kocar Benjamin et al, 2004;Langner et al, 2001;Yokoyama et al, 1993).…”
Section: Arsenic In the Environmentmentioning
confidence: 99%